Vaccine Development (IntechOpen, 2022)
Vaccination is the most effective and scientifically based means of protection against infectious diseases, especially in this era of the COVID-19 pandemic. This book examines several issues related to the development of vaccines against viral, bacterial, and parasitic infections.